1983
DOI: 10.3354/meps014009
|View full text |Cite
|
Sign up to set email alerts
|

Influences of bag dimensions on the development of enclosed plankton communities during POSER

Abstract: During POSER (Plankton Observations with Simultaneous Enclosures in Rosfjorden) natural plankton communities were enclosed by large plastic bags anchored in situ. Enclosures of different dimensions, ranging in depth from 3 to 40 m and containing 1.5 to 30 m3 of water, facilitated the study of dimension effects of the enclosure on the development of the plankton inside. When comparing mean values in small bags with those of the total mixed layer of large bags, phytoplankton development was very similar in large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…fish, seabirds and mammals), and to approximate vertical mixing of water column and small-scale shear occurring in nature (Menzel and Steele, 1978;Carpenter, 1996). Enclosure effects may also influence food web dynamics to varying degrees, creating trophic interactions that can differ with mesocosm dimension and which may deviate from those of the natural system intended to be mimicked (Kuiper et al, 1983;French andWatts, 1989, Petersen et al, 2009). Despite these difficulties and the intense debate they have spurred over the past decades (e.g.…”
Section: U Riebesell Et Al: a Mobile Sea-going Mesocosm Systemmentioning
confidence: 99%
“…fish, seabirds and mammals), and to approximate vertical mixing of water column and small-scale shear occurring in nature (Menzel and Steele, 1978;Carpenter, 1996). Enclosure effects may also influence food web dynamics to varying degrees, creating trophic interactions that can differ with mesocosm dimension and which may deviate from those of the natural system intended to be mimicked (Kuiper et al, 1983;French andWatts, 1989, Petersen et al, 2009). Despite these difficulties and the intense debate they have spurred over the past decades (e.g.…”
Section: U Riebesell Et Al: a Mobile Sea-going Mesocosm Systemmentioning
confidence: 99%
“…Many of these are little more than common sense, bul they should be enumerated both for completeness and because they impose constraints on the design of a mixing system. The most important are (1) Size: There are minimum dimensions for mesocosms based on organism size and behavior (Guanguo 1990), light extinction (Menzel & Case 1977), trophic complexity (Kuiper et al 1983), and sampling requirements. Size also is an issue with regard to the state of the turbulence (Osborn & Scotti 1996).…”
Section: General Considerations and Constraintsmentioning
confidence: 99%
“…Recent studies have shown that particularly surface or wall effects in enclosures tend to increase bacterial growth and activity, and that these effects are more pronounced in small volumes (<3 1) than in larger enclosures (30 m3; Kuiper et al 1983, Ferguson et al 1984, see also Grice & Reeve 1982. In addition, Ferguson et al (1984) found that manipulation of natural seawater by filtration (3 pm) increased the growth rate of bacteria.…”
Section: Ecological Significancementioning
confidence: 99%